An RRI for the present moment: relational and 'well-up' innovation. Issue 2 (4th May 2021) - Albertson, Kevin; de Saille, Stevienna; Pandey, Poonam; Amanatidou, Effie; Arthur, Keren Naa Abeka; Van Oudheusden, Michiel; Medvecky, Fabien
ABSTRACT: The ultimate framing of the first iteration of RRI as enabling smart, inclusive, sustainable growth had as much to do with the financial crisis then engulfing the Eurozone as meeting the goals of the Lisbon Treaty. Now we have come to the end of Horizon 2020, it is presently unclear how RRI will continue to be addressed as it is mainstreamed into Horizon Europe. In this Perspective, we will argue that discussions about placing responsibility at the centre of innovation should not solely be aimed at promoting GDP-measured growth. Our vision must be longer, more global, more transformative. In this short piece, we explore the possibilities arising through extending 'responsibility' to an a-growth approach to innovation, one which emphasises the relational dimensions of responsible innovation through the concept of 'well up' economics.